Molecular mechanism and enzymological studies of dye-decolorizing peroxidases (DyPs) from Thermomonospora curvata and Enterobacter lignolyticus - Shrestha, Ruben (Kansas State University, 2017)
Dye-decolorizing peroxidases (DyPs) comprise a new family of heme peroxidases, which have received much attention due to their potential applications in degradation of lignin and anthraquinone dyes. In this research, studies of two types of DyPs are carried out and reported in the following three sections. The first section includes the identification and characterization of class-A TcDyP from Thermomonospora curvata, a thermophilic actinomycete found in composted manure. The TcDyP was found to be highly active toward a wide range of substrates including phenolic lignin model compounds. Transient- and steady state- kinetics involving wild-type (wt) and mutant TcDyPs revealed that Asp220 and Arg327 are essential for compound I formation and reduction of compound II to resting state is the rate-limiting step. Additionally, replacement of His312 and Arg327 shifted the redox potential (E°′) to a more negative value. In the second section, the residues involved in the radical generation and substrate oxidation were explored. TcDyP contains 7 tryptophans and 3 tyrosines, which are the likely candidates of protein radicals and substrate oxidation sites. Crystal structure of TcDyP solved at 1.75Å revealed Trp263, Trp376 and Tyr332 as surface-exposed protein radical sites. Further studies using site-directed mutagenesis, steady-state and stopped-flow kinetics determined that the Trp263 is also one of the surface-exposed substrate oxidation sites. The Trp376 was characterized as the residue essential for covalent crosslinking of the enzyme units and an off-pathway electron sink. The highly conserved Tyr332 was found to be unimportant for substrate oxidation due to its extremely narrow surface exposure. The final section involves mechanistic study of a class-B DyP from Enterobacter lignolyticus (ElDyP), a bacterium capable of growing on lignin anaerobically. The crystal structure of ElDyP revealed the presence of two heme access channels measuring at ~3.0 and 8.0 Å in diameter and a water molecule as the sixth ligand to the heme center. Bisubstrate Ping-Pong mechanism was found operational in the catalytic cycle of ElDyP, in which conformational change of the enzyme resting state was proposed as the final step and the rate limiting step in the presence of ABTS. Microscopic events leading to Compound I formation was analyzed using D₂O₂. A kinetic isotope effect (KIE) of 2.4 at pD 3.5 suggested that Compound 0 is formed initially with protonation/deprotonation as the rate-limiting step. Compound I was directly reduced to the enzyme resting state via a 2-electron process, for which the rate increases as the pH decreases. Based on viscosity effect and solvent KIE (sKIE) with the reducing substrate, aquo release was found to be mechanistically important. Distal aspartate was proposed as the key residue that modulates the acidic pH optimum in Compound I reduction. These findings will pave the way for engineering DyPs for their applications in the degradation of lignin and synthetic dyes.
Keywords: DyP; Peroxidase; Dye; Lignin; Enzymology